The C-test as predictor of the academic success of international students. Issue 10 (26th November 2021) - Daller, Michael; Müller, Amanda; Wang-Taylor, Yixin
ABSTRACT: The present article gives an overview of several studies on the predictive validity of the C-test. In the first part of the article, we discuss the construct validity of this test format. Only if the underlying construct of this test is understood, can a justification for high predictive validity be made. In the second part, we discuss several previous studies where the C-test format is used to predict the study and training success of international students. The third part discusses the findings of two as yet unpublished studies on the predictive validity of the C-test. We wish to contribute to the ongoing discussion of the validity of the C-test and argue that it is not only a language test, but also a test of processing speed which is related to working memory. For international students, processing speed in English as a foreign language is related to vocabulary knowledge, which includes statistical knowledge about the probability of words occurring in a given context as well as the probability of words following or preceding each other. The C-test taps precisely into these aspects of language proficiency which explains its high predictive validity for the study success of international students.